Magnesium and the Problem of Fabrication in Your Product - Dow Chemical Company (1952)
Color print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. Describes how the use of Dowmetal magnesium material eases the work of production facilities. The material is advertised as lightweight, strong, corrosion-resistant, and able to be shaped and produced in a variety of forms. Depicts an extended hand, from which circular magnesium pieces are flying. Includes a brief description of Dowmetal's application to the United States' defense effort. The Dowmetal logo, a hand holding a winged ingot of magnesium, is located in the bottom right of the advertisement. Found on page 75 of Time Magazine, February 4, 1952 issue.
Keywords: Advertising; Dow Chemical Company; Advertising, Industrial; Chemical Industry; Magnesium alloys; Mineral industries